Ayurvedic Management of Spinal Muscular Atrophy - Pavan HR; Seetharamu M.S; Lohith BA (AYUSHDHARA, 2025)
Spinal Muscular Atrophy (SMA) is one among the genetic disorder characterised by progressive muscle atrophy and weakness. It is an autosomal recessive condition with an incidence of approximately 1 in 11,000, primarily affecting infants and children with varying severity. Although not specifically described in classical Ayurvedic texts, spinal muscular atrophy (SMA) may be interpreted as a Kulaja Vyadhi or an Anukta Vyadhi. This study aims to evaluate the efficacy of the Panchakarma approach in improving the quality of life in an SMA patient. A single case study was conducted on a 19-year-old male diagnosed with SMA, who visited SDM Ayurvedic hospital with complaints of difficulty in climbing stairs, loss of balance, and challenges in getting up from the ground. The patient underwent Panchakarma therapy, including Udvartana, Basti, Abhyanga, Prishta Seka, and Shashtika shali Pinda Swedana. After undergoing two cycles of Panchakarma treatment at six-month intervals, the patient’s symptoms were reassessed. DEXA scanning showed significant improvement, and overall quality of life was greatly enhanced. The results suggest that the Panchakarma line of treatment is effective in improving the quality of life in SMA patients and could be a breakthrough in its management.